2023
DOI: 10.1021/acs.inorgchem.3c00769
|View full text |Cite
|
Sign up to set email alerts
|

[AsCCAs]-Coordinated Rhenium Hydrides and Their Reactivities Toward Unsaturated Hydrocarbons, Heterocumulenes, and CO2

Abstract: An [AsCCAs] ligand featuring a central alkyne and two flanking arsenic donors was employed for the synthesis of a trihydrido rhenium complex, while the corresponding phosphorus ligand was shown to be less suited. The reactivity of the former trihydride [AsCCAs]ReH 3 (3) was examined in detail, which revealed that two alternative reaction channels may be entered in dependence of the substrate. Upon reaction of 3 with PhC�CPh, ethylene, and CS 2 , monohydrides of the general formula [AsCCAs]Re(L)H with L = η 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 103 publications
1
6
0
Order By: Relevance
“…A comparison of the alkyne units in 2-As, 5, and 3-As revealed that the CC bond lengths steadily decrease in the sequence d CC (2-As) > d CC (5) ≫ d CC . As expected for a 4e − alkyne donor, a rather long CC bond distance of 1.3209 (18) was found in 2-As, which shortens to 1.310(4) upon formal oxidation to 5. In 3-As, a significantly shorter alkyne CC distance of 1.277(3) Å was determined, suggesting that the latter alkyne is best interpreted as a 2e − donor, as also inferred from its 13 C{ 1 H} NMR signal at 134.9 ppm.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…A comparison of the alkyne units in 2-As, 5, and 3-As revealed that the CC bond lengths steadily decrease in the sequence d CC (2-As) > d CC (5) ≫ d CC . As expected for a 4e − alkyne donor, a rather long CC bond distance of 1.3209 (18) was found in 2-As, which shortens to 1.310(4) upon formal oxidation to 5. In 3-As, a significantly shorter alkyne CC distance of 1.277(3) Å was determined, suggesting that the latter alkyne is best interpreted as a 2e − donor, as also inferred from its 13 C{ 1 H} NMR signal at 134.9 ppm.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…31 Å). 18 These differences between 9 and 11 are expected given that π-donation from the nitride is thought to diminish π-donation from the alkyne (vide supra). In the solid state, an unexceptional Re�N triple bond (∼1.66 Å) with v Re�N = 1050 cm −1 (ATR-IR) was found in 11, which is in line with a dominating metal nitride interaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations